The Integration of Artificial Intelligence in English Language Teaching: Opportunities and Challenges - Saydibragimova Yulduzxon (Zien Journals, 2024)
The advent of artificial intelligence (AI) has initiated a transformative era across various sectors, including education. This thesis explores the integration of AI in English Language Teaching (ELT), highlighting its potential benefits, challenges, and implications for educators and learners. By analyzing current AI applications in language education, this paper aims to provide a comprehensive overview of how AI can enhance language acquisition, personalize learning experiences, and support teachers in their pedagogical practices.
Keywords: effective learning; language acquisition; AI systems; real-life conversations